2020
DOI: 10.1371/journal.pone.0233528
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and epidemiology of hepatitis B and C viruses in pregnant women in Spain. Risk factors for vertical transmission

Abstract: Background & aim Worldwide, measures are being implemented to eradicate hepatitis B (HBV) and C (HCV) viruses, which can be transmitted from the mother during childbirth. This study aims to determine the prevalence of HBV and HCV in pregnant women in Spain, focusing on country of origin, epidemiological factors and risk of vertical transmission (VT). Methodology Multicentre open-cohort study performed during 2015. HBV prevalence was determined in 21870 pregnant women and HCV prevalence in 7659 pregnant women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
4
2
Order By: Relevance
“…HCV prevalence was comparable to studies from Spain [ 27 ], India [ 28 ], Tanzania [ 29 ], and Bahirdar [ 8 ] that found 0.26%, 0.21%, 0.3%, and 0.26%, respectively. Nevertheless, it was lower than the results in East Wollega (8.07%) [ 30 ]; in Yemen (8.5%) [ 18 ]; in Western Ethiopia (8.1%) [ 31 ]; in Iran (1.33%) [ 32 ]; and in Nigeria (2.7%) [ 33 ].…”
Section: Discussionsupporting
confidence: 81%
“…HCV prevalence was comparable to studies from Spain [ 27 ], India [ 28 ], Tanzania [ 29 ], and Bahirdar [ 8 ] that found 0.26%, 0.21%, 0.3%, and 0.26%, respectively. Nevertheless, it was lower than the results in East Wollega (8.07%) [ 30 ]; in Yemen (8.5%) [ 18 ]; in Western Ethiopia (8.1%) [ 31 ]; in Iran (1.33%) [ 32 ]; and in Nigeria (2.7%) [ 33 ].…”
Section: Discussionsupporting
confidence: 81%
“…The seroprevalence of hepatitis b and c viruses in this study is higher than that of 6.25% in Ethiopia and 8.1% in the western part of Nigeria This may be attributed to the lower sociocultural status of these women, polygamous marriage practices, cultural practices like tribal marks, and early marriages practices in the setting where this study was conducted (11,12). Also, the seroprevalence of HBV was found to be higher than the findings from studies done in other parts of Nigeria and other LMICs where the seroprevalence ranged from 4.6%-9.7% (11,12,13,14,15,16,17,18,19,20,21,22), but lower than the finding in Angola of 25.7% seroprevalence (23). A similar study in Central Nigeria also found a high prevalence of 19.5% and this may be due to the exclusion of women who had been vaccinated for HBV from the study (24).…”
Section: Discussioncontrasting
confidence: 56%
“…Five hundred and forty-six (43.6%) women did not have complete information on the registers, either they were not screened or they were screened but the results were not documented in the registers. The ages of the women ranged from 15 The seroprevalence of HBV and HCV in the study population over the three years was 11.6% and 6.5% respectively, while the total seroprevalence of hepatitis b and c was 18.1%%. HBV and HCV had their highest prevalence in 2019 with a prevalence of 15.8% for HBV and 9.4% for HCV.…”
Section: Resultsmentioning
confidence: 99%
“…HBV infection varied greatly in different regions and populations [ 7 , 10 , 11 ]. Several studies had reported HBV prevalence among pregnant women in some provinces of China or other countries [11][12][13][14] and the prevalence among women preparing for pregnancy [ 7 , 15 ]. The prevalence of HBV infection in women of reproductive age and pregnant women in China varied from 3.87% to 9.98% in previous studies [15] .…”
Section: Introductionmentioning
confidence: 99%